INCREASING COMPETITIVE ADVANTAGE OF TOMATO FARMING BASED ON COST STRUCTURE WITH BUSINESS INTELLIGENCE APPROACH IN MINAHASA, INDONESIA - Tulungen, Franky Reintje; Lempas, Jety Deisye; Lengkong, Jemly; Oping, Joy M; Lintong, Heibert (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Tomatoes are an important food for humans whose production and price must be maintained so that the commodity remains available to humans. The objectives of the study are (i) analyzing the cost structure of tomato farming in Minahasa district, Indonesia, (ii) analyzing strategies to increase the competitive advantage of tomato farmers based on the cost structure of tomato farming with a business intelligence (BI) approach in Minahasa district, Indonesia and (iii) provide recommendations for the concept of tomato farming technology based on improving the structure of tomato farming costs in Minahasa district, Indonesia. This research uses a quantitative approach with the BI method and was carried out in the tomato production center of Minahasa district, North Sulawesi. The results found that (i) the production cost structure of Apple Tomato farming, namely variable costs of Rp 53,600,054.44 / ha or 78.74 percent and fixed costs of Rp 14,475,057.00 / ha or 21.26 percent. Based on cost structure, the variable cost that can be reduced is human labor cost and the fixed cost that can be reduced is stake cost. The recommended innovations that can be applied are using tractors to replace human labor to make beds, and replacing bamboo stakes with plastic pipes. This innovation can increase the profit of tomato farming from Rp 99,122,272.83 per ha to Rp 108,456,162.83 or an increase of Rp 9333890.00 (9.42%) per ha and the BEP price from Rp 2,300 per kg to Rp 1,987.82 per kg or reduce by Rp 312.18 (13.57%) per kg.